5 - Mutation des espaces agricoles et quête de sécurité alimentaire dans les interfaces urbaines-rurales du Sénégal : étude de cas de Ziguinchor - Diédhiou, Sécou Omar; Cissé, Idrissa; Dabo, Alioune Badara (Africa Development, 2022)
The city of Ziguinchor was built on a marriage of convenience with the small peasantry and has for several years been undergoing major urban transformations that affect the entire rural space. This is manifested in a rapid population increase that creates unprecedented needs, particularly in terms of employment, mobility, housing, and food. These transformations lead to land predation facilitated by poorly identified norms and governance, that result in the occupation of the last local agricultural spaces. These agricultural spaces (valleys, lowlands, and plateaus) are essential in local food production, but also for housing, city equipment and infrastructure. We are witnessing a gradual transformation of these spaces into residential housing estates, despite the urgency of food issues. This article focuses on a cross-cutting theme, that of food in a city primarily dominated by urban projects. It is particularly interested in changes in agricultural landscapes, and farming families faced with land precariousness, raisind questions about the place of agriculture in territorial development, and the ability to farm locally, in particular, food production for the population.